2009
DOI: 10.1254/jphs.09048fp
|View full text |Cite
|
Sign up to set email alerts
|

Obovatol Enhances Docetaxel-Induced Prostate and Colon Cancer Cell Death Through Inactivation of Nuclear Transcription Factor-κB

Abstract: Abstract. Nuclear transcription factor-κB (NF-κB) is constitutively activated in prostate and colon cancers and is related with the resistance of cancer cells against chemotherapeutics. Previously, we found that obovatol, an active compound isolated from Magnolia obovata, inhibited cancer cell growth through inhibition of NF-κB activity. We investigated here whether obovatol could sensitize cancer cells against docetaxel through inhibition of NF-κB activity in prostate cancer (LNCaP and PC-3) and colon cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…These factors include the Y-box binding protein-1, CCAAT-binding transcription factor 2, activating transcription factor 4, zincfinger factor 143, the nuclear transcription factor-B, the microphthalmia-associated transcription factor, the forkhead transcription factor O, and mitochondrial transcription factor A (Torigoe et al, 2005;Lee et al, 2009;Lei and Quelle, 2009;Li et al, 2009;Keenen et al, 2010). Hirano et al (2010) reported that p300/CBP-associated factor (PCAF) was overexpressed in human prostate and epidermal cisplatin-resistant P/CDP6 and HeLa/CP4 cells.…”
Section: A Transcription Factors Play a Major Role In Cisplatin Resimentioning
confidence: 99%
“…These factors include the Y-box binding protein-1, CCAAT-binding transcription factor 2, activating transcription factor 4, zincfinger factor 143, the nuclear transcription factor-B, the microphthalmia-associated transcription factor, the forkhead transcription factor O, and mitochondrial transcription factor A (Torigoe et al, 2005;Lee et al, 2009;Lei and Quelle, 2009;Li et al, 2009;Keenen et al, 2010). Hirano et al (2010) reported that p300/CBP-associated factor (PCAF) was overexpressed in human prostate and epidermal cisplatin-resistant P/CDP6 and HeLa/CP4 cells.…”
Section: A Transcription Factors Play a Major Role In Cisplatin Resimentioning
confidence: 99%
“…Deoxypodophyllotoxin and podophyllotoxin (POD) are two well-known naturally occurring aryltetralin lignans. Both compounds are cytotoxic (1), and their derivatives such as etoposide (ETO) (2,3), teniposide (4), and etopophos have potential clinical use as antitumor agents (5,6). However, due to the drug resistance developed by cancer cells as well as side effects associated with the use of these agents in the clinic (including myelosuppression, neutropenia, and nausea), the search for new effective anticancer analogs remains an intense area of research (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, to be effective, DTX must be administered at such high doses that can induce significant toxicity. 9,17 To overcome this drawback, combination therapies have been developed; DTX combined with tyrosine kinase or bcl-2 inhibitors are currently in Phase II studies for treating CRPC. 17 Drug-delivery assemblies consisting of a nanocarrier, a targeting agent, and DTX have also been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current regimen requires the administration of high doses of DTX, which causes toxic reactions and thereby precludes the use of DTX as a monotherapy. 9 To reduce toxicity and to improve the survival and quality of life of CRPC patients, novel therapeutic strategies targeting the molecular basis of androgen-and chemo-resistance of prostate cancer using a reduced but equieffective dose of DTX should be developed.…”
Section: Introductionmentioning
confidence: 99%